STRUKTUR KEPEMILIKAN PERUSAHAAN SEBAGAI MEKANISME PEMBENTUKAN PRINSIP KONSERVATISME UNTUK MENCIPTAKAN RESPON PASAR - Yulianthy Ho; Suwandi Ng; Paulus Tangke (SIMAK, 2019)
The aim of this research is to investigate whether institutional ownership and family ownership have an impact to conservatism, whether institutional ownership, family ownership and conservatism have an impact to ERC, and whether conservatism is able to mediate the impact of institutional ownership and family ownership to ERC. The population used in this research is all non-financial companies listed on the Indonesia Stock for the period 2014-2017. The number of samples used amounted 147 companies each year, selected using purposive sampling method. Path analysis is used to analyze the data in this research. The first substructure equation of this research shows that institutional ownership and family ownership have a positive impact on conservatism. The second substructure equation shows that institutional ownership positively affects the ERC, while family ownership and conservatism negatively affect the ERC. The results of a sobel test indicate that conservatism fails to mediate the impact of institutional ownership and family ownership towards ERC. The implications of this research is that investors can consider institutional ownership, family ownership, and the application of conservatism principles that can affect the response to the firms’ earnings quality as measured by earnings response coefficient (ERC).